Financial Accounting: An Input/Output Approach (Book). - Sterling, Robert R.; Knutson, Peter H. (The Accounting Review, 1971)
Abstract Reviews the book "Financial Accounting: An Input/Output Approach," by William J. Schrader, Robert E. Malcom and John J. Willingham.